The liverwort genus Metzgeria (Metzgeriaceae, Marchantiophyta) in Thailand - Sukkharak, Phiangphak; Chantanaorrapint, Sahut (Phytotaxa, 2020)
The taxonomic account of the genus Metzgeria in Thailand is presented based on herbarium specimens and recent collections from field surveys. Five species of Metzgeria including M. consanguinea, M. furcata, M. kinabaluensis, M. leptoneura, and M. lindbergii are recognized. Of these, M. kinabaluensis is newly reported to Thailand. A key to the species, descriptions and illustrations of each species are provided. Ecology and geographical distribution of the species are noted. In addition, M. pubescens is excluded from the country.